La memoria e il mito in Apocaypse Now e Cuore di tenebra (Mantichora. Italian Journal of Performance Studies, 2020)
Heart of Darkness by Joseph Conrad and film adaptation by Francis Ford Coppola, Apocalypse Now, analyze the theme of memory and the importance of remembrance, in particular in its degraded version proposed by the Harlequin, mask which is present both in the novel and in the film.